Australasian Consumer Fraud Taskforce: results of the 2012 online consumer fraud survey - Alice Hutchings
The Australasian Consumer Fraud Task Force has conducted a range of fraud prevention and awareness raising activities since 2006. This report presents the results of the 2012 online consumer fraud survey. Foreword Each year, since 2007, the Australian Institute of Criminology (AIC) has collected information on consumer scams by conducting an online survey of Australians who have received scam invitations during the preceding 12 months. The research is conducted on behalf of the Australasian Consumer Fraud Taskforce (ACFT), which is comprised of 22 government regulatory agencies and departments in Australia and New Zealand who work alongside private sector, community and non-government partners to prevent fraud of this nature. In order to understand the dynamics of consumer fraud victimisation, the ACFT has conducted a range of fraud prevention and awareness-raising activities over the last eight years. The annual survey seeks to obtain a snapshot of the public’s exposure to consumer scams, to assess the range of ways in which scams can affect victims and their families, to determine how victims respond and to identify emerging typologies and issues that could be used to inform fraud prevention initiatives. Survey respondents are not representative of the whole Australian population, as the sample is made up of those individuals who choose to participate, although in 2012, over 1,500 people completed the survey with good levels of representation from all states and territories, and other demographic categories. This report presents the results of the survey conducted in conjunction with the 2012 campaign, Slam scams! Press ‘delete’, throw it out, shut the door or just hang up. The campaign theme was concerned with scam delivery methods that focused on raising awareness about the many ways in which scammers try to deliver scam invitations. A phone call, SMS, mobile application, house visit, letter, email, fax, blog, online chat or dating service—scammers will use any of these means to target victims. The primary message was simple—stop the contact at the point of delivery; if you don’t engage with a scammer in the first place, you can avoid being scammed. As in previous years, a high proportion of respondents had received a scam invitation (95%), with almost a quarter responding to the scam in some way. Unfortunately, eight percent reported having lost money—approximately $8,000 per person or almost $850,000 in total. The most prevalent scam type involved fraudulent lotteries, while this year, the second-most prevalent scam concerned computer support scams, which are sometimes a means of extracting payments for non-existent services from victims or, on other occasions, a means of installing malicious software that can be used to extract personal information at a later time. In terms of delivery methods, although email continued to be the most common method by which scams were delivered, the use of landline and mobile telephones (including SMS) to target potential scam victims increased. This report also includes some additional information on online shopping scams—the subject of the consumer fraud awareness week in June 2013. The prevalence of scams targeting those who sell or buy high-value items online, such as motor vehicles, was high in 2012, indicating a need for enhanced awareness of the risks involved in this form of consumer activity